Studies on adequate supply of Methionine + Cystine in diets of juvenile turbot (Psetta maxima) - Klatt, Simon Friedrich (2016)
The supply of crude protein (CP) plays a key role in the feeding of turbot (Psetta maxima). For the essential sulfur-containing amino acids (methionine - met; cyst (e) ine - Cys), inadequate use of protein sources can lead to deficiency situations, but also toxic effects in case of oversupply. Therefore, the objectives of the present thesis were to define a range from which the fish needs to reach the concentration at which the supply of Met + Cys is toxic (1. & 2.experiment). In addition, the contribution of rapeseed protein concentrate (RPC) with regard to the Met + Cys supply was assessed in two further experiments (3. & 4.experiment). In the 1.experiment, the lower and upper critical concentrations (LCC, UCC) of Met + Cys were determined for turbot. This results to the LCC for relative growth (% live weight (LW) day-1) (RG) at 1.25% (± 0.02 s.e.) Met + Cys in diet DM (2.26% in CP). The UCC was 2.68 % (± 0.21 s.e.) (4.85 % in CP). In the second test, the UCC was determined again because of the still insufficient data of the UCC in the first test. The values for RG were here at 2.27 % (± 0.44 s.e.) (3.84 % in CP) in diet DM. In the 3.experiment, the intestinal availability of Met + Cys in RPC and fish meal (FM) was determined. Intestinal availability was 65.3 % for RPC and 95.7 % for FM. The lower performance of the fish fed with RPC diets in the 4.experiment can be explained by the ANF (antinutritional factors) in the RPC, but not by Met + Cys, compared to the higher performance of the fish fed with FM-diets. The values for the LCC and UCC of Met + Cys determined in these studies provide important information on the optimization of rations regarding the demand for these amino acids, as well as the critical use of Met + Cys-rich protein sources such as RPC. Für eine bedarfsgerechte Fütterung des Steinbutt (Psetta maxima) kommt der Versorgung mit Rohprotein (XP) eine Schlüsselrolle zu. Für die essentiellen schwefelhaltigen Aminosäuren (Methionin - Met; Cyst(e)ine- Cys) können bei nicht adäquatem ...